2023
DOI: 10.1101/2023.06.04.543525
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Amyloid β Induces Lipid Droplet-Mediated Microglial Dysfunction in Alzheimer’s Disease

Abstract: Several microglia-expressed genes have emerged as top risk variants for Alzheimer′s disease (AD). Impaired microglial phagocytosis is one of the main proposed outcomes by which these AD-risk genes may contribute to neurodegeneration, but the mechanisms translating genetic association to cellular dysfunction remain unknown. Here we show that microglia form lipid droplets (LDs) upon exposure to amyloid-beta (Aβ), and that their LD load increases with proximity to amyloid plaques in brains from human patients and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 94 publications
0
15
0
Order By: Relevance
“…Excess fatty acids are often stored in triglyceride-rich lipid droplets, which we observed by microscopy (Figure 1G,H). Other studies have observed increased levels of microglial lipid droplets in the contexts of aging, disease, and inflammation 15,23,24,27,32 , suggesting that lipid accumulation in microglia is a central biological phenomenon and operates in multiple contexts. To further understand the functional consequences of lipid accumulation we chose to interrogate whether lipid accumulation was necessary for microglial activation or whether it was an epiphenomenon.…”
Section: Lps-activated Microglia Display Neutral Lipid Accumulationmentioning
confidence: 94%
“…Excess fatty acids are often stored in triglyceride-rich lipid droplets, which we observed by microscopy (Figure 1G,H). Other studies have observed increased levels of microglial lipid droplets in the contexts of aging, disease, and inflammation 15,23,24,27,32 , suggesting that lipid accumulation in microglia is a central biological phenomenon and operates in multiple contexts. To further understand the functional consequences of lipid accumulation we chose to interrogate whether lipid accumulation was necessary for microglial activation or whether it was an epiphenomenon.…”
Section: Lps-activated Microglia Display Neutral Lipid Accumulationmentioning
confidence: 94%
“…Lipid extraction from the frozen microglial cell pellets was done following Bligh and Dyer protocol with slight modifications 88,89 . Briefly, the pellets were thawed at 4 °C for 10 mins, after which, cold methanol, and HPLC-grade chloroform were added in a ratio of 2:1.…”
Section: Methodsmentioning
confidence: 99%
“…A volume of 8μL of diluted lipid extract was introduced into the Agilent Jet Stream (AJS) ion source of the mass spectrometer by flow injection for each MRM method. Briefly, MRM methods were established for 10 lipid classes and spanned 1497 individual lipid species 89,90 . Lipid classes of interest were phosphatidylcholine (PC), phosphatidylethanolamine (PE), phosphatidylglycerol (PG), phosphatidylinositol (PI), phosphatidylserine (PS), acyl carnitine (CAR), cholesterol ester (CE), diacylglycerol (DG), triacylglycerol (TG), and sphingomyelin (SM).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, besides the interplay between sex hormones and ApoE risk loci, the drastic metabolic changes occurring during the critical period of perimenopause in women also increase oxidative stress in the brain [191], which may further lead to accumulation of LDs in specific brain cell types and contribute to sex-specific AD vulnerability. For example, female microglia show an increase of several long-chain species of TAGs with more LDs; such LDladen microglia that are chronically exposed to Aβ exhibit a dysfunctional phagocytosis [201].…”
Section: Sex Differences Of Lipids In Ad and Npdsmentioning
confidence: 99%